Are Early Somatic Embryos of the Norway Spruce (Picea abies (L.) Karst.) Organised? - Petrek, Jiri; Zitka, Ondrej; Adam, Vojtech; Bartusek, Karel; Anjum, Naser A; Pereira, Eduarda; Havel, Ladislav; Kizek, Rene (PloS one, 2015)
BACKGROUND: Somatic embryogenesis in conifer species has great potential for the forestry industry. Hence, a number of methods have been developed for their efficient and rapid propagation through somatic embryogenesis. Although information is available regarding the previous process-mediated generation of embryogenic cells to form somatic embryos, there is a dearth of information in the literature on the detailed structure of these clusters. METHODOLOGY/PRINCIPAL FINDINGS: The main aim of this study was to provide a more detailed structure of the embryogenic tissue clusters obtained through the in vitro propagation of the Norway spruce (Picea abies (L.) Karst.). We primarily focused on the growth of early somatic embryos (ESEs). The data on ESE growth suggested that there may be clear distinctions between their inner and outer regions. Therefore, we selected ESEs collected on the 56th day after sub-cultivation to dissect the homogeneity of the ESE clusters. Two colourimetric assays (acetocarmine and fluorescein diacetate/propidium iodide staining) and one metabolic assay based on the use of 2,3,5-triphenyltetrazolium chloride uncovered large differences in the metabolic activity inside the cluster. Next, we performed nuclear magnetic resonance measurements. The ESE cluster seemed to be compactly aggregated during the first four weeks of cultivation; thereafter, the difference between the 1H nuclei concentration in the inner and outer clusters was more evident. There were clear differences in the visual appearance of embryos from the outer and inner regions. Finally, a cluster was divided into six parts (three each from the inner and the outer regions of the embryo) to determine their growth and viability. The innermost embryos (centripetally towards the cluster centre) could grow after sub-cultivation but exhibited the slowest rate and required the longest time to reach the common growth rate. To confirm our hypothesis on the organisation of the ESE cluster, we investigated the effect of cluster orientation on the cultivation medium and the influence of the change of the cluster's three-dimensional orientation on its development. Maintaining the same position when transferring ESEs into new cultivation medium seemed to be necessary because changes in the orientation significantly affected ESE growth. CONCLUSIONS AND SIGNIFICANCE: This work illustrated the possible inner organisation of ESEs. The outer layer of ESEs is formed by individual somatic embryos with high metabolic activity (and with high demands for nutrients, oxygen and water), while an embryonal group is directed outside of the ESE cluster. Somatic embryos with depressed metabolic activity were localised in the inner regions, where these embryonic tissues probably have a very important transport function.
Keywords: tetrazoliové soli; jedle; Abies; Norway; smrk; Norsko; Picea; Tetrazolium Salts; Plant Proteins; rostlinné proteiny